2000
DOI: 10.1111/j.1365-2885.2000.00271.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of plasma pharmacokinetics and bioequivalence of ceftiofur sodium in cattle after a single intramuscular or subcutaneous injection

Abstract: Comparison of plasma pharmacokinetics and bioequivalence of ceftiofur sodium in cattle after a single intramuscular or subcutaneous injection. J. vet. Pharmacol. Therap. 23,[273][274][275][276][277][278][279][280] Ceftiofur sodium, a broad-spectrum cephalosporin, is active against gram-positive and gram-negative pathogens of veterinary importance. This study was designed to compare the bioequivalence of the sodium salt in cattle after a single intramuscular (i.m.) or subcutaneous dose (s.c.) of 2.2 mg ceftiofu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
1
5

Year Published

2004
2004
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 7 publications
1
11
1
5
Order By: Relevance
“…, 2002). In this study, the peak plasma concentration ( C max ) was 10.34 ± 1.24 μ g/mL, this result is lower than that reported by Brown et al. , 2000 in cattle 13.9 μ g/mL, Brown et al.…”
Section: Mean ± Sd Plasma Pharmacokinetic Parameters Of Ceftiofur Incontrasting
confidence: 69%
“…, 2002). In this study, the peak plasma concentration ( C max ) was 10.34 ± 1.24 μ g/mL, this result is lower than that reported by Brown et al. , 2000 in cattle 13.9 μ g/mL, Brown et al.…”
Section: Mean ± Sd Plasma Pharmacokinetic Parameters Of Ceftiofur Incontrasting
confidence: 69%
“…, 1990). The LOQ of this assay has ranged between 0.15 and 0.5 μg/mL (Brown et al. , 2000; Pille et al.…”
Section: Discussionmentioning
confidence: 99%
“…Pharmacokinetics of ceftiofur have been described for several animals, including cattle (Brown et al, 2000;Okker et al, 2002), pigs (Brown et al, 1999), mares (Jonker, 1997), sheep (Craigmill et al, 1997), goats (Courtin et al, 1997), and llama and alpaca (Drew et al, 2004). In most reports, however, pharmacokinetics were determined for ceftiofur in plasma.…”
Section: Discussionmentioning
confidence: 99%
“…Although early postpartum use of ceftiofur has been described in several studies, there is only limited information about the pharmacokinetics of ceftiofur in bovine uterine tissue. Pharmacokinetics and bioequivalence of ceftiofur in plasma have been compared for intramuscular and subcutaneous administration (Brown et al, 2000). Previous authors suggested similar therapeutic efficacy for the 2 routes of administration.…”
Section: Introductionmentioning
confidence: 99%